MEDIA VIDEO PODCAST AKTIVITAS FISIK SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS BAGI REMAJA ANGGOTA UKS - Ester Jessica Marbun; Ridwan Setiawan (Jurnal Kesehatan Siliwangi, 2025)
The prevalence of diabetes mellitus (DM) among adolescents is concerning, with 89,128 cases in West Java in 2023, and Bandung Regency ranking second with 59,205 cases. A lack of physical activity is a major contributing factor, increasing the risk of obesity and Type 2 DM. Therefore, preventive efforts through education on the importance of physical activity are essential. Therefore, preventive efforts through education on the importance of physical activity are needed. Objective: This study aimed to develop a Spotify-based podcast promoting physical activity to prevent DM among School Health Unit (UKS) members at SMPN 1 Margahayu, using the ADDIE model. Method: The study employs the R&D (Research and Development) model ADDIE (Analysis, Design, Development, Implementation, Evaluation). The study was conducted at SMPN 1 Margahayu with a sample population of 44 students. Results: Analysis phase identified identified the need for interactive media with a young female presenter, simple language, animations, clear text, and aerobic demonstrations. Design phase included script development, question frameworks, and storyboarding. Development phase produced a 30-minute podcast video. The resulting 30-minute podcast received high ratings from content (93.75%) and media experts (92.3%). Implementation over three sessions, it increased students knowledge by 31.34%. Conclusion: Evaluation phase of the podcast video distribution shows effectiveness in enhancing engagement, improving information retention, and fostering adolescents' interest in physical activity for the prevention of diabetes mellitus.